Foreign Learners' Needs for Interactive Digital BIPA Materials: Evidence from Indonesian Language Programs - Martriwati; Nani Solihati; Zamah Sari (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to examine the factors influencing foreign learners’ needs for interactive digital Indonesian language learning materials (Bahasa Indonesia bagi Penutur Asing/BIPA) by integrating technological and cultural dimensions within the Technology Acceptance Model (TAM) framework. Methods: A quantitative explanatory survey design was employed involving 210 foreign learners enrolled in BIPA programs across several institutions in Indonesia. Data were collected using a structured questionnaire measuring user interface quality, digital interactivity, cultural relevance, perceived ease of use, perceived usefulness, and learners’ needs. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. Findings: The results revealed that user interface quality and digital interactivity significantly influenced perceived ease of use, while digital interactivity and perceived ease of use significantly affected perceived usefulness. Perceived usefulness was found to positively influence foreign learners’ needs for interactive digital BIPA materials. Cultural relevance also had a significant direct effect on learners’ needs, although its influence on perceived usefulness was not significant. These findings indicate that both technological usability and cultural authenticity play important roles in shaping learners’ expectations and preferences toward digital BIPA materials. Research Implications: The findings provide practical guidance for BIPA educators, instructional designers, and educational institutions in developing user-centered, interactive, and culturally responsive digital learning materials. Emphasis on intuitive interfaces, meaningful interactivity, and authentic cultural content can enhance learner engagement and learning effectiveness. Originality: This study extends the Technology Acceptance Model by integrating cultural relevance and digital interactivity into a single framework to explain foreign learners’ needs for interactive digital BIPA materials, offering a more comprehensive understanding of technology-enhanced language learning in intercultural contexts.